2006
DOI: 10.3114/sim.55.1.147
|View full text |Cite
|
Sign up to set email alerts
|

A multi-gene phylogeny for species of Mycosphaerella occurring on Eucalyptus leaves

Abstract: Species of the ascomycete genus Mycosphaerella are regarded as some of the most destructive leaf pathogens of a large number of economically important crop plants. Amongst these, approximately 60 Mycosphaerella spp. have been identified from various Eucalyptus spp. where they cause leaf diseases collectively known as Mycosphaerella Leaf Disease (MLD). Species concepts for this group of fungi remain confused, and hence their species identification is notoriously difficult. Thus, the introduction of DNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 33 publications
4
79
0
1
Order By: Relevance
“…Mycosphaerella aurantia) was found associated with leaf spots on Blepharocalyx salicifolius. Although there has been some confusion regarding the identification of this species, with Hunter et al (2006) suggesting that it is likely the same as Teratosphaeria africana, isolate UY1382 obtained from Blepharocalyx salicifolius grouped strongly with other T. aurantia isolates, including that of the ex-type (Maxwell et al 2003). Morphological characteristics of ascospores observed in this study also showed they did not have constrictions at the median septum, as described for T. aurantia (Maxwell et al 2003).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Mycosphaerella aurantia) was found associated with leaf spots on Blepharocalyx salicifolius. Although there has been some confusion regarding the identification of this species, with Hunter et al (2006) suggesting that it is likely the same as Teratosphaeria africana, isolate UY1382 obtained from Blepharocalyx salicifolius grouped strongly with other T. aurantia isolates, including that of the ex-type (Maxwell et al 2003). Morphological characteristics of ascospores observed in this study also showed they did not have constrictions at the median septum, as described for T. aurantia (Maxwell et al 2003).…”
Section: Discussionsupporting
confidence: 51%
“…Mycosphaerella heimii) (Crous et al, 2013). Although Hunter et al (2006) considered Pal. heimii to represent a member of a species complex due to the difficulty differentiating this species from Pal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological identification is difficult for species of the Mycosphaerellaceae and the Teratosphaeriaceae because they typically grow slowly in culture and many also sporulate only on host tissue (Crous 1998;Crous et al 2001a;Hunter et al 2004Hunter et al , 2006. Where morphology can be used for identification, it is based on the associated but morphologically variable anamorph genera (Crous 1998;Crous et al 2001a;Hunter et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This group of fungi included approximately 3,000 species names with diverse ecological roles representing endophytes, pathogens and saprobes (Corlett 1995;Crous et al 2000;Hunter et al 2004Hunter et al , 2006Crous et al 2009c;Hunter et al 2011). The pathogens in these genera include important leaf and shoot pathogens of a number of hosts, including Eucalyptus and other trees in the Myrtaceae.…”
Section: Introductionmentioning
confidence: 99%